Two 'Oldowan' assemblages in the Plio-Pleistocene deposits of the Orce region, southeast Spain - Gibert, J.; Gibert, Ll; Iglesias, A.; Maestro, E.
Stone artefacts reported from the Orce region (Grenada, Spain) indicate a first human presence in western Europe as early as the Plio-Pleistocene boundary, making a long chronology for European hominids against the claims for a briefer human presence. Excavations of Barranco León-5 and Fuentenueva-3a in 1995 have produced two groups of lithic artefacts of 'Oldowan' type, seen as the most ancient of western Europe by fauna associations and palaeomagnetic study.